2020
DOI: 10.14710/jaa.16.2.18-38
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Intellectual Capital on Firm Value With Earnings Management as a Moderating Variable: a Study in Financial Service Companies Listed on Indonesia Stock Exchange (Idx)

Abstract: This research aims to examine the influence of intellectual capital performance on firm value and the moderating influence of earnings management on the relationship of intellectual capital with firm value in financial service companies listed on the Indonesia Stock Exchange during 2015 – 2018. Based on the population of 90 companies per year, a test of 69 sample companies that met the criteria of purposive sampling was conducted. The panel data regression technique is used to analyze the data. The findings sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
1
1
1
Order By: Relevance
“…Intellectual capital in a company will give a positive signal to investors because high intellectual ability can indicate the company's ability to maximize the use of its resources, and the company could get big profits in the future. This research is in line with previous research on the effect of intellectual capital on company value conducted by (Fanni & Fuad, 2019;Ni et al, 2020), which shows that intellectual capital has a positive influence on company value because intellectual capital information in annual reports can show prospects of the company and become a decision-making tool for investors and stakeholders. The company's intellectual capital, explained broadly, will provide investors with confidence that the company can achieve maximum value in competition with a sustainable competitive advantage.…”
Section: Theoretical Reviewsupporting
confidence: 90%
See 2 more Smart Citations
“…Intellectual capital in a company will give a positive signal to investors because high intellectual ability can indicate the company's ability to maximize the use of its resources, and the company could get big profits in the future. This research is in line with previous research on the effect of intellectual capital on company value conducted by (Fanni & Fuad, 2019;Ni et al, 2020), which shows that intellectual capital has a positive influence on company value because intellectual capital information in annual reports can show prospects of the company and become a decision-making tool for investors and stakeholders. The company's intellectual capital, explained broadly, will provide investors with confidence that the company can achieve maximum value in competition with a sustainable competitive advantage.…”
Section: Theoretical Reviewsupporting
confidence: 90%
“…The results of this study are supported by (Subaida et al, 2018;Suwandi & Susilawati, 2023), which states that intellectual capital does not affect company value due to the possibility of low investor awareness or ability to read good signals regarding company intellectual capital. This research differs from that conducted by (Fuad, 2019;Ni et al, 2020), who states that intellectual capital positively affects company value because companies with employees with broad insight will have advantages for renewal and better company image.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In research conducted by previous researchers, it has been proven that in companies in the banking sector, intellectual capital has a positive effect on firm value (Abdul Fanni, 2019;Vitolla et al, 2020;Xu & Liu, 2020;Yustyarani & Yuliana, 2020;Zaytsev et al, 2020). Research on good corporate governance as an amplifier of the influence of intellectual capital on firm value that has been carried out by previous researchers also proves that the results can have a positive effect .…”
Section: Introductionmentioning
confidence: 87%
“…In research conducted by Çam & Özer (2022) and found that intellectual capital and its components have lagged effects on market values of firms. Abdul Fanni (2019) and found that intellectual capital has a positive and significant effect on firm value. H1…”
Section: Hypothesis Development the Effect Of Intellectual Capital On...mentioning
confidence: 99%